Effects of slow internet on academic library staff productivity and job satisfaction (2024)
This paper investigated the effects of slow internet on academic library staff productivity and job satisfaction of academic library staff using the University of Ibadan library as a case in focus. Data Collection Methods. The study employed a qualitative research method, guided by a phenomenological research paradigm, using Focus Group discussions for data collection. The responses were presented and discussed objectively. Data Analysis. NVivo software was used for qualitative data analysis to enhance the depth of qualitative research by providing data management technique and facilitate complex analyses, and support robust reporting. Results and Discussion. Findings of the study revealed that slow internet may have serious consequences on library staff, their operations, and productivity including; decreased output, staff dissatisfaction, and hampered user services etcetera. The study recommends that universities and library management invest in faster, more reliable internet, implement hybrid systems to provide alternative resources during technological limitations, ensure librarians are adaptable in managing slow internet challenges, and encourage librarians to maintain a positive mindset to avoid frustration and job dissatisfaction. Conclusion. This research addresses a gap in the literature by examining how internet speed impacts library staff productivity and satisfaction, providing insights for enhancing library services and staff well-being amidst technological challenges.